Bioavailability of Glucoraphanin and Sulforaphane from High‐Glucoraphanin Broccoli. Issue 18 (8th March 2018) - Sivapalan, Tharsini; Melchini, Antonietta; Saha, Shikha; Needs, Paul W.; Traka, Maria H.; Tapp, Henri; Dainty, Jack R.; Mithen, Richard F.
Abstract : Scope: Broccoli accumulates 4‐methylsulphinylbutyl glucosinolate (glucoraphanin) which is hydrolyzed to the isothiocyanate sulforaphane. Through the introgression of novel alleles of the Myb28 transcription factor from Brassica villosa, broccoli genotypes have been developed that have enhanced levels of glucoraphanin. This study seeks to quantify the exposure of human tissues to glucoraphanin and sulforaphane following consumption of broccoli with contrasting Myb28 genotypes. Methods and results: Ten participants are recruited into a three‐phase, double‐blinded, randomized crossover trial (NCT02300324), with each phase comprising consumption of 300 g of a soup made from broccoli of one of three Myb28 genotypes (Myb28 B/B, Myb28 B/V, Myb28 V/V ). Plant myrosinases are intentionally denatured during soup manufacture. Threefold and fivefold higher levels of sulforaphane occur in the circulation following consumption of Myb28 V/B and Myb28 V/V broccoli soups, respectively. The percentage of sulforaphane excreted in 24 h relative to the amount of glucoraphanin consumed varies among volunteers from 2 to 15%, but does not depend on the broccoli genotype. Conclusion: This is the first study to report the bioavailability of glucoraphanin and sulforaphane from soups made with novel broccoli varieties. The presence of one or two Myb28 V alleles results in enhanced delivery of sulforaphane to the systemic circulation. Abstract : The pharmacokinetics of glucoraphanin and sulforaphane is assessed in a three‐phase, double‐blinded, randomized crossover trial with three types of broccoli soups with varying Myb28 genotypes (Myb28 B/B, Myb28 B/V, Myb28 V/V ). This study provides evidence that enhancing glucoraphanin content in broccoli results in increased levels of sulforaphane in the plasma.